Consequences of COVID-19 on adolescents in Arizona: A longitudinal study protocol - Leybas Nuño, Velia; Mantina, Namoonga M.; Dawodu, Oriyomi; Dykinga, Maureen; Carr, Dametreea L.; Pogreba-Brown, Kristen; Cordova-Marks, Felina; Jehn, Megan; Peace-Tuskey, Kimberly; Barraza, Leila; Garcia-Filion, Pamela (Frontiers in Public Health, 2022)
Introduction The long-term impact of COVID-19 is unknown. We developed a 5-year prospective cohort study designed to generate actionable community-informed research about the consequences of COVID-19 on adolescents ages 12–17 years in Arizona. Methods The study has two primary outcomes: 1) acute and long-term outcomes of COVID-19 illness and 2) symptoms of depression and anxiety. Data is collected using an online survey with plans to integrate qualitative data collection methods. The survey is administered at baseline, 4, and 8 months in year one, and annually in years two through five. This study is informed by Intersectionality Theory, which considers the diverse identities adolescents have that are self and socially defined and the influence they have collectively and simultaneously. To this end, a sample of variables collected is race/ethnicity, language usage, generational status, co-occurring health conditions, and gender. Additional measures capture experiences in social contexts such as home (parent employment, food, and housing security), school (remote learning, type of school), and society (racism). Results Findings are not presented because the manuscript is a protocol designed to describe the procedure instead of report results. Discussion The unique contributions of the study is its focus on COVID-19 the illness and COVID-19 the socially experienced pandemic and the impact of both on adolescents.